The Effect Of Institutional Ownership And Leverage On Agency Costs - Situmorang, Yosefh Sendi; Lesmana, Desy (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2023)
This study aimed to determine the effect of institutional ownership and Leverage on agency cost by focusing on manufacturing companies listed on the Indonesia Stock Exchange with a research period 2018 – 2020. The data used were secondary data. The population in this study was manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling method and obtained a total of 360 samples. Hypothesis testing was done by multiple regression analysis. The results of this study indicated that institutional ownership hurt agency cost and Leverage hurt agency cost.